Low-temperature effect on seismic life-cycle cost estimation for isolated highway bridges with high damping rubber bearings - Jie Shen; Tong Guo; Ji Dang; Akira Igarashi; Shuling Hu; M. Shahria Alam (Soil Dynamics and Earthquake Engineering, 2026)

Recent advances in the formation, characterization, and applications of starch-polyphenol complexes: A review - Bo Han; Qianhan Ma; Shuling Yan; Shiyin Jia; Yao Hu; Hao Xu; Siyuan Liu; Hao Zhang; Pengjie Wang; Jiayue Guo (Food Chemistry, 2026)

A novel technique to characterize hydrophobic and hydrophilic pore for shale reservoirs by nuclear magnetic resonance and vapor adsorption - Shuling Xiong; Rui Yang; Lin Yuan; Aiwei Zheng; Qinhong Hu; Zhiliang He; Hassan Dehghanpour (Journal of Asian Earth Sciences, 2026)

Chronic Fluoride Exposure from Brick Tea Consumption Disrupts Bone Remodeling and Contributes to Bone Loss in Chinese Population with Skeletal Fluorosis - Hongjiang Long; Yubo Liu; Pinggui Lei; Ting Hu; Zhijuan Shao; Yu Luo; Shuling Zhang; Jinshu Li; Peng Luo; Zhenting Zhang; Shaofeng Wei (Biological Trace Element Research, 2026)

A novel numerical analysis method for the stability of sediment void-type energy storage salt cavern and its application in Tai’an, China - Xiaopeng Liang; Xiuli Ding; Wanrui Hu; Hongling Ma; Shuling Huang; Xilin Shi; Rui Cai; Zhen Zeng; Xuan Wang (Tunnelling and Underground Space Technology, 2026)

Seismic risk assessment of isolated highway bridges with high damping rubber bearings considering temperature variations - Jie Shen; Ji Dang; Akira Igarashi; Shuling Hu; Yuki Hamada; Takehiko Himeno; M. Shahria Alam (Engineering Structures, 2026)

Novel distributed parameter models for self-centering dual rocking core system with multiple rocking sections - Chunxue Dai; Shuling Hu; Wei Wang; M. Shahria Alam; Theodoros L. Karavasilis (Soil Dynamics and Earthquake Engineering, 2025)

Machine learning in earthquake engineering: A review on recent progress and future trends in seismic performance evaluation and design - Shuling Hu; Tong Guo; M. Shahria Alam; Yuji Koetaka; Elyas Ghafoori; Theodoros L. Karavasilis (Engineering Structures, 2025)

1-MCP regulates taste development in cold-stored peach fruit through modulation of sugar, organic acid, and polyphenolic metabolism - Huijuan Zhou; Zhengwen Ye; Lufan Wang; Shiying Zhang; Ziyi Yuan; Mingshen Su; Xianan Zhang; Jihong Du; Xiongwei Li; Minghao Zhang; Yang Hu; Shuling Shen; et al. (Postharvest Biology and Technology, 2025)

Performance and recentering demands of partially self-centering BRBFs in the life-cycle span - Ruibin Zhang; Shuling Hu; Tong Guo (Engineering Structures, 2025)

Delayed Detached-Eddy Simulations of Aerodynamic Variability During Carrier-Based Aircraft Landing with a Domain Precursor Inflow Method - Jiawei Fu; Ruifan Hu; Hong Wang; Ke Xu; Shuling Tian (Journal of Marine Science and Engineering, 2025)
Flight tests and wind tunnel experiments face difficulties in investigating the impact of aircraft carrier air-wake on the landing process. Meanwhile, numerical methods generally exhibit low overall computational efficiency in solving such problems. To address the computational challenges posed by the disparate spatiotemporal scales of the ship air-wake and aircraft motion, a domain precursor inflow method is developed to efficiently generate unsteady inflow boundary conditions from precomputed full-domain air-wake simulations. This study investigates the aerodynamic variability of carrier-based aircraft during landing through the turbulent air-wake generated by an aircraft carrier, employing a hybrid RANS-LES methodology on dynamic unstructured overset grids. The numerical framework integrates a delayed detached-eddy simulation (DDES) model with a parallel dynamic overset grid approach, enabling high-fidelity simulations of coupled aircraft carrier interactions. Validation confirms the accuracy of the precursor inflow method in reproducing air-wake characteristics and aerodynamic loads compared to full-domain simulations. Parametric analyses of 15 distinct landing trajectories reveal significant aerodynamic variability, particularly within 250 m of the carrier, where interactions with island-generated vortices induce fluctuations in lift (up to 25%), drag (18%), and pitching moments (30%). Ground effects near the deck further amplify load variations, while lateral deviations in landing paths generate asymmetric forces and moments. The proposed methodology demonstrates computational efficiency for multi-scenario analysis, providing critical insights into aerodynamic uncertainties during carrier operations.

Transcriptomics analysis reveals the regulatory role of PsERF3 in anthocyanin biosynthesis of ‘Taoxingli’ plum fruit in response to MeSA treatment - Lichuan Lou; Xiaoli Hu; Jiao Cheng; Yuan Cheng; Mengyao Yin; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2025)

Seismic risk assessment of partially self-centering braced frames designed with multiple-objective-based method - Shuling Hu; Ruibin Zhang (Engineering Structures, 2025)

Correction: A New Safety Control Method of Blasting Excavation in High Rock Slope with Joints - Yingguo Hu; Zhaowei Yang; Shuling Huang; Wenbo Lu; Gen Zhao; Cong Luo (Rock Mechanics and Rock Engineering, 2024)

Inhibitiory mechanism of phloretin on xanthine oxidase and its synergistic effect with allopurinol and febuxostat - Jiaqi Wen; Shuling Chen; Le Deng; Xinru Chen; Xiaoyu Jiang; Xing Hu; Deming Gong; Guowen Zhang (Food Bioscience, 2024)

Probabilistic evaluation of spectral acceleration demands on light secondary systems supported by partially self-centering structures - Shuling Hu; Bing Qu; Canxing Qiu; Ruibin Zhang (Engineering Structures, 2024)

Self-centering dual rocking core system with viscous dampers in additional rocking sections - Chunxue Dai; Shuling Hu; Wei Wang (Soil Dynamics and Earthquake Engineering, 2024)

Self-sacrificed construction of versatile nanoadjuvant for synergistically enhanced immunogenic cell death and improved anti-tumor immunity - Peng Hu; Xiaowen Peng; Shuang Zhao; Fan Li; Guoye Yang; Wujie Guo; Shuling Yu; Jianjun Cheng; Juan Cen; Jiahua Shi (Chemical Engineering Journal, 2024)

Isoliquiritigenin retards starch digestion by increasing resistant starch content and inhibiting the activities of α-amylase and α-glucosidase - Yushi Wei; Le Deng; Shuling Chen; Xing Hu; Guowen Zhang (Food Bioscience, 2024)

Hybrid self-centering braces with NiTi-SMA U-shaped and frequency-dependent viscoelastic dampers for structural and nonstructural damage control - Shuling Hu; Yuji Koetaka; Zhi-Peng Chen; Songye Zhu; M. Shahria Alam (Engineering Structures, 2024)

Post-earthquake repairability-based methodology for enhancing steel MRFs - Shuling Hu; Xuhong Zhou; Ke Ke; M. Shahria Alam; Taotao Shi (Engineering Structures, 2024)

Source-Specific Ecological Risk of Atmospheric PM2.5-Bound Metals and Implications for Air Pollution Control: A Regional Perspective from China - Weiwei Lin; Hedi Zhang; Yuming Lai; Shuling Zhuang; Qiannan Wei; Shaojie Fu; Dejian Mai; Luan Yuan; Qing Wei; Dingli Yue; Qiansheng Hu (Exposure and Health, 2024)

Influence of extractable organic components on shale wettability: Dongyuemiao member of Jurassic Ziliujing formation in the Fuxing area, Eastern Sichuan Basin - Weihang Zhang; Rui Yang; Zhiliang He; Hanyong Bao; Hui Yu; Shuling Xiong; Yuanjia Han; Qinhong Hu; Sheng He (Marine and Petroleum Geology, 2023)

Role of antenatal anxiety in the relationship between maternal exposure to nitrogen dioxide and small for gestational age: A birth cohort study - Qiannan Wei; Weiwei Lin; Hedi Zhang; Yuming Lai; Shuling Zhuang; Zhenyan Han; Qingqing Wang; Lijie Wang; Wenzhuo Li; Li Wen; Hongying Hou; Qiansheng Hu (Science of The Total Environment, 2023)

Hybrid self-centering dual rocking core system for seismic resilience by controlling both structural and nonstructural damage - Shuling Hu; Ruibin Zhang; Wei Wang (Engineering Structures, 2023)

Probabilistic residual displacement-based design for enhancing seismic resilience of BRBFs using self-centering braces - Ruibin Zhang; Shuling Hu; Wei Wang (Engineering Structures, 2023)

The effects of prenatal PM2.5 oxidative potential exposure on feto-placental vascular resistance and fetal weight: A repeated-measures study - Weiwei Lin; Yuming Lai; Shuling Zhuang; Qiannan Wei; Hedi Zhang; Qiansheng Hu; Peng Cheng; Manman Zhang; Yuhong Zhai; Qingqing Wang; Zhenyan Han; Hongying Hou (Environmental Research, 2023)

PsbZIP1 and PsbZIP10 induce anthocyanin synthesis in plums (Prunus salicina cv. Taoxingli) via PsUFGT by methyl salicylate treatment during postharvest - Shuling Shen; Xiaoli Hu; Jiao Cheng; Lichuan Lou; Chen Huan; Xiaolin Zheng (Postharvest Biology and Technology, 2023)

Performance improvement of flapping propulsions from spanwise bending on a low-aspect-ratio foil - Tianlong Lin; Wei Xia; Rosario Pecora; Kun Wang; Shuling Hu (Ocean Engineering, 2023)

Explainable machine learning models for probabilistic buckling stress prediction of steel shear panel dampers - Shuling Hu; Wei Wang; Yongchang Lu (Engineering Structures, 2023)

Life-cycle benefits estimation of self-centering building structures - Shuling Hu; Wei Wang; M. Shahria Alam; Ke Ke (Engineering Structures, 2023)

Mechanistic insights into the detoxification of Cr(VI) and immobilization of Cr and C during the biotransformation of ferrihydrite-polygalacturonic acid-Cr coprecipitates - Hanyue Zhang; Yang Lu; Zhuozhi Ouyang; Wenjing Zhou; Xinyue Shen; Kun Gao; Shuling Chen; Yang Yang; Shiwen Hu; Chongxuan Liu (Journal of Hazardous Materials, 2023)

Temperature effects on microbial dissolved organic matter metabolisms: Linking size fractions, fluorescent compositions, and functional groups - Gang Tang; Binrui Li; Bowei Zhang; Shiwen Hu; Shuling Chen; Tong Liu; Qianqian Wang; Han Qiao; Xing Zheng (Science of The Total Environment, 2023)

Experimental investigation of thermodynamic and kinetic behaviors from water vapor adsorption on four typical clay minerals - Shuling Xiong; Manfei Chen; Hui Yu; Weihang Zhang; Qinhong Hu; Sheng He; Rui Yang (Gas Science and Engineering, 2023)

Hybrid test and numerical study of beam-through frame enhanced by friction spring-based self-centering rocking core - Ruibin Zhang; Wei Wang; Chengyu Yang; Shuling Hu; M. Shahria Alam (Engineering Structures, 2023)

Correction to: Spatial pattern of the effects of human activities on the land surface of China and their spatial relationship with the natural environment - Shuling Hu; Bin Yu; Shen Luo; Rongrong Zhuo (Environment, Development and Sustainability, 2022)

Spatial pattern of the effects of human activities on the land surface of China and their spatial relationship with the natural environment - Shuling Hu; Bin Yu; Shen Luo; Rongrong Zhuo (Environment, Development and Sustainability, 2022)

Correction to: Data-driven analysis and evaluation of regional agriculture for high quality development of Anhui Province in the Yangtze River Delta - Fan Liu; Cui Wang; Yingyan Zhang; Shuling Zhou; Yaliu Yang; Xue Wu; Fagang Hu; Conghu Liu (Environmental Science and Pollution Research, 2022)

Data-driven analysis and evaluation of regional agriculture for high-quality development of Anhui Province in the Yangtze River Delta - Fan Liu; Cui Wang; Yingyan Zhang; Shuling Zhou; Yaliu Yang; Xue Wu; Fagang Hu; Conghu Liu (Environmental Science and Pollution Research, 2022)

A New Safety Control Method of Blasting Excavation in High Rock Slope with Joints - Yingguo Hu; Zhaowei Yang; Shuling Huang; Wenbo Lu; Gen Zhao (Rock Mechanics and Rock Engineering, 2020)

Role of mTOR complex in IGF-1 induced neural differentiation of DPSCs - Dan Huang; Shuling Shen; Ming Cai; Lin Jin; Jun Lu; Ke Xu; Jinlong Zhang; Guijuan Feng; Yingzi Hu; Ke Zheng; Xingmei Feng (Journal of Molecular Histology, 2019)

Rapid detection of infectious hypodermal and hematopoietic necrosis virus (IHHNV) by real-time, isothermal recombinase polymerase amplification assay - Xiaoming Xia; Yongxin Yu; Linghao Hu; Manfred Weidmann; Yingjie Pan; Shuling Yan; Yongjie Wang (Archives of Virology, 2015)

Oct4 is expressed in Nestin-positive cells as a marker for pancreatic endocrine progenitor - Hong Wang; Shuling Wang; Jiang Hu; Yaxian Kong; Shen Chen; Lingsong Li; Liying Li (Histochemistry and Cell Biology, 2009)